Draft genome sequences of Listeria monocytogenes, isolated from fresh leaf vegetables in Owerri City, Nigeria - Nwaiwu, Ogueri; Moura, Alexandra; Thouvenot, Pierre; Rees, Catherine; Leclerc, Alexandre; Lecluit, Marc (American Society for Microbiology, 2017)
Here, we report the draft genome sequences of three Listeria monocytogenes isolates from fresh leaves collected in Nigeria, belonging to sequence types ST5 and ST155 (sublineages SL5 and SL155, respectively).